(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1913)
The oldest accurate plan is a drawing attributed to a J Slezer and thought to have been produced during a visit in 1675. The second drawing is a large pen and ink drawing, which is a bird’s-eye view from the south of the Castle and its surroundings, probably produced after 1689 and before 1707. The third very detailed drawing is dated 1746 and signed W. Adam’s. This must be William Adam of Maryburgh in Fife, who held the appointment for a time as King’s Master Mason. A further two plans belong to the Office of Works and are dated 1725 and 1735.